Risco biológico em unidades de preparo e administração de medicamentos de serviços de urgência e emergência da cidade de Goiânia‐GO - MENDONÇA, Katiane Martins (2010)
This study focuses on the biological risk in the daily work of professional nursing staff entered in the medication system in areas of emergency care. The goal was to evaluate the biological risk for professionals in the nursing staff who work in the preparation and administration of medicines, and to clients, of emergency services of large public hospitals, of the city of Goiania GO. And the specifics were: to describe the physical structure, material´s and human´s resources in the units of preparation and administration of medicines in areas of emergency care in large public hospitals, in Goiânia-GO, to identify risk´s behaviors (considered when the call to a standard precaution is not met) related to exposure to biological material for the professional nursing staff who work in the preparation and administration of medicines and to customers in emergency services and the emergence of large public hospitals, in Goiânia-GO, to characterizing accidents with biological material among health nursing staff who act in the preparation and administration of drugs in emergency rooms of large public hospitals, of the city of Goiânia-GO and to identify the biosafety´s measures adopted by professional nursing staff, who act in the preparation and administration of drugs in emergency rooms of large public, hospitals, of the city of Goiânia-GO in respect to the biological risk. This is a descriptive of a cross-sectional study did in the three large public hospitals of the city of Goiania-GO that has in its structure the sector of urgency and emergency with the preparation and administration of medicines units. The study was approved by the Ethics Commissions in Research of the three hospitals that participated of this research. Data were collected through two check-list to observe the professional´s behaviors and the organizational structure (material and physical) of the units. The physical structure of the units of preparation and administration drugs in the sectors of emergency care can be regarded as inappropriate for the worker's health and may to interfere with care. Consented to participate in the study 130 professionals, who signed a Term of Informed Consent, after the observation period. Most of them were female and nursing technicians and performed 292 procedures for preparation and administration of drugs in the collection of datas. There was a low adherence to the practice of handwashing, and no professional performed the correct technique. Low adherence to protection items, individual and collective. Several risk´s behaviors for exposure to biological material were observed in the practice of professionals nursing in the units of preparation and administration of drugs in the areas of emergency care, emphasizing the segregation and disposal of waste, inadequate transportation of drugs, failure to maintain aseptic chain, the act of re-encasing needles and how to re-wrap it, poor compliance to the items of protection, the low rate of handwashing and improper use, or not recommended, the resources available. Were witnessed, eight accidents involving biological material among professionals in the nursing team, and none made the notification. The individual care over collective care was observed in this study. The results show a need for change not only in the physical and material resources in situations of emergency is necessary to encourage compliance with standard precautions, but also to seek new ways to minimize the biological risk for both worker's health as for the patients, through the actual behaviors observed, often repetitive, which increase the risk referred to in each situation. The nurse presents with an important role to integrate the team and coordinate its activities and may, at first, after identifying behaviors, plan and implement an education in the reality they are experiencing.